The development of the health promotion program on maternal anemia: Qualitative study - Sirikanok Klankhajhon; Kornkarn Pansuwan; Pratuma Rithpho; Hidayat Arifin (Jurnal Keperawatan Padjadjaran, 2023)
Background: Iron deficiency anemia in pregnant women is a crucial global health problem. Iron deficiency anemia is impacted on health during antenatal, labor and postpartum period. Although the national policy provides the preventive and solving the maternal anemia, the statistics of maternal anemia  are still high. Purpose: The aim of the study is to develop a health promotion program that is suitable for maternal anemia. Methods: Qualitative research was used to develop the health promotion program  on maternal anemia through in-depth interviews. Ten pregnant women who had hematocrit less than 33 volume percentages or hemoglobin less than 11 g/dl and five healthcare professionals were selected by purposive sampling. A total of fifteen participants were interviewed based on the semi-structured questionnaire for 30-45 minutes per case at the antenatal care clinic, Watbot hospital, Phitsanulok, Thailand. The period of the study was six months from the first of August 2022 until the end of January 2023. Results: Thematic analysis was used to analyze the data and identified three main themes: 1) encouragement the attitude of self-care during pregnancy; 2) accessibility of the program ; and 3) practical use of the program  and integrating the program  based on the context of pregnant women and healthcare professionals. Conclusion: The health promotion program was developed suitable for maternal anemia. The tailored program should be tested in terms of feasibility, accessibility, and practical use. It will support pregnant women with anemia, develop a key  performance index of maternal and child health, decrease risks and complications, and promote maternal and child health based on the various contexts.